Classroom Observation for the Professional Development of Myanmar University Lecturers in a Singapore Cross-Cultural Context: Perception of Abilities and Learning Based on ‘Nine Events of Instruction’ - Lam, Siew Hong (European Journal of Social Science Education and Research, 2020)
Continuing professional development is important for improving and reforming teaching.Classroom observation of others’ teaching has been used for the professional development of eight lecturers from three Myanmar universities who visited the Department of Biological Sciences, National University of Singapore over a period of three weeks.To bridge the socio-cultural and educational background differences, Gagné’s ‘Nine events of instruction’ was used as a pedagogical framework to guide and evaluate the classroom observation and learning as it is well-established for instructional design and resonate well with educators.This study aimed to evaluate the participants’ abilities and their learning through classroom observation based on their perceptions of the ‘nine events of instruction’.The study found that most of the participants have positive views of their abilities in relation to the ‘nine events’, especially in practicing the early events of instruction. The classroom observation has benefitted them with respect to the ‘nine events’, particularly ‘Informing the Students of the Objective/Outcome’, ‘Stimulating Recall of the Prior Knowledge’ and ‘Presenting Information/Content/Stimulus’.Notably, ‘Assessing Performance’ was the most perceived ‘event of instruction’ that the participants wanted to improve on and that the participants perceived will benefit Myanmar lecturers the most.Qualitative feedbacks by the participants revealed lessons learned, their potential applicability and desires to reform and share.The study further demonstrated that the ‘nine events of instruction’ is a useful pedagogical framework for guiding and evaluating perception of abilities and learning in classroom instruction and observation for continuing professional development in a cross-cultural context.